Effect of Electron-Beam Treatment on the Elemental Composition and Static Displacements of Atoms in the Nearsurface Layer of Cr-Mn-N Austenitic Steel; AIP Conference Proceedings; Vol. 2167 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2019 (AMHS'19) - Narkevich N.; Surikova N.; Vlasov I.; Narkevich V.; Deryugin Ye.; Perevalova O. (2019, 2019)
Title screen